Socio-Demographic Characteristics of Teenage Pregnancy: Experience of 50 Cases of Bangladesh (Journal of Science Foundation, 2018)
Background: Teenage pregnancy is a huge problem in developed as well as developing countries.Objective: The purpose of the present study was to see the socio-demographic characteristics of teenage pregnant mother.Methodology: This cross-sectional study was conducted in the Department of Obstetrics and Gynecology, Dhaka Medical College & Hospital, Dhaka, Bangladesh and Sir Salimullah Medical College & Mitford Hospital, Dhaka, Bangladesh from April to July 1999 for a period of four (4) months. The teenager mothers with the age group of 11 to 19 years who were admitted in the study period was selected as study population. At the time of entry, all relevant parameters like religion, residence, occupation, education and monthly income were recorded in a predesigned data sheet.Result: A total number of 50 teenager mothers were recruited for this study. Majority of the study population were Muslim which was 45(90.0%) cases followed by Hindu which was 3(6.0%) cases. Maximum were non-city dweller which was 26(52.0%) cases followed by city and slum dwellers which were 16(32.0%) cases and 8(16.0%) cases respectively. Majority of the study were housewife which was 49(98.0%) cases. Monthly income was less than 3000 taka in 29(58.0%) cases. Majority of the study population were completed the primary education level which was 26(52.0%) cases. Married was found in 49(98.0%) cases.Conclusion: In conclusion Muslim non-city dwellers housewife were the most common group of teenager motherJournal of Science Foundation 2018;16(1):3-7